NILAI-NILAI DASAR PERJUANGAN HMI: SUATU IKHTIAR MEWUJUDKAN KERUKUNAN HIDUP UMAT BERAGAMA DI INDONESIA - Dwi Wahyuni (JIA (Jurnal Ilmu Agama), 2016)
Maturity  of  religious  understanding  is  a  major  effort  to  achieve  religious  harmony  in Indonesia. Muslim Students Association (Himpunan Mahasiswa Islam)’s Core Values of Struggle is the starting point to develop, to disseminate and to implement the religious maturity. At least, there are  three  aspects  of  its  core  values  that  important  to  achieve  religious  harmony  in  Indonesia, namely:  Monotheism,  the  humanitarian  aspects  and  social  aspects.  These  three  aspects  will  bring interfaith relations more open, tolerant and harmonious. Religious people fully realize that all men are ungodliness in the same God, the Almighty God, all religious people are given the freedom to understand,  to  appreciate  and  to  practice  their  religion  in  full  conviction.  Religious  people  also should  to  believe  that  all  human  beings  are  basically  good  so  thatthey  can  view  a  positive  and optimistic  attitude  to  other  religious  believes,  instead  of  being  suspicious  of  one  another. Furthermore, inter-religious relations need the real cooperation in everyday life. All religions need cooperation  against  common enemies, those are  social injustice, poverty, ignorance, violations of human  rights  and  the  tyranny  that  alienates  the  awareness  of  Almi  God.  All  religions  have  a responsibility to the real work.